USING STORIES TO INTEGRATE NUTRITION AND HEALTH EDUCATION FOR CHILDREN IN PRESCHOOL - Cao Thi Thu Hoai, Tran Thi Nhung (Tạp chí Khoa học, 2024)
Nutrition and health education are the main content in physical development education for preschool children. To help children develop some good habits and behaviors in eating and hygiene to prevent disease, teachers can use many teaching resources. This study analyzes the advantages of the story works and directions for using them to integrate nutrition and health education for preschool children. Content analysis method, direct interview method, and operational product research method have been used. The results show that stories that can be used to integrate nutrition education for children in preschool are relatively rich and diverse. Teachers can use these stories to educate children about the habit of maintaining physical hygiene and educating children about hygienic and nutritious eating, thereby improving the quality of care, nurturing and education of children at preschool educational establishments.